Concessionary Financing Programs for the Water and Sanitation Sector in China - World Bank (Washington, DC, 2014)
China's water and sanitation sector faces challenges from rapid urbanization and industrialization, urban diversification, large investment needs, water scarcity, water pollution, and ecological degradation. This policy note addresses 'concessionary finance.' It is intended to provide a briefing for Chinese government officials who formulate policies for the water and sanitation sector. This note is not intended to provide recommendations on which policies to adopt, but rather to facilitate understanding of the policy options, how to choose among them, and where and how various options have been used in practice. Good water and sanitation services are essential for economic growth, public health, and environmental protection. However, these services can be difficult to finance. When utilities do not have sufficient capital, they under-invest and this will adversely affect the quality of services the utilities provide. Many governments run targeted concessionary financing programs as a method of helping utilities raise the needed capital. International experience has shown that well designed concessionary financing programs can additionally be employed as incentives to successfully improve utility efficiency, sector governance, or both. This policy note draws on successful case studies from concessionary finance programs in other countries.